Unravelling the role of anaerobic metabolism (pta-ackA) and virulence (misL and ssa) genes in Salmonella Heidelberg shedding using chicken infection model - Monte, Daniel F. M. [UNESP]; Saraiva, Mauro M. S. [UNESP]; Cabrera, Julia Memrava [UNESP]; de Almeida, Adriana Maria [UNESP]; de Freitas Neto, Oliveiro Caetano; Barrow, Paul A.; Junior, Angelo Berchieri [UNESP] (Springer Nature, 2024)
The mechanism of colonisation of the chicken intestine by Salmonella remains poorly understood, while the severity of infections vary enormously depending on the serovar and the age of the bird. Several metabolism and virulence genes have been identified in Salmonella Heidelberg; however, information on their roles in infection, particularly in the chicken infection model, remains scarce. In the present publication, we investigated three Salmonella Heidelberg mutants containing deletions in misL, ssa, and pta-ackA genes by using signature-tagged mutagenesis. We found that mutations in these genes of S. Heidelberg result in an increase in fitness in the chicken model. The exception was perhaps the pta-ackA mutant where colonisation was slightly reduced (2, 7, 14, and 21 days post-infection) although some birds were still excreting at the end of the experiment. Our results suggest that for intestinal colonisation of the chicken caecum, substrate-level phosphorylation is likely to be more important than the MisL outer membrane protein or even the secretion system apparatus. These findings validate previous work that demonstrated the contribution of ackA and pta mutants to virulence in chickens, suggesting that the anaerobic metabolism genes such as pta-ackA could be a promising mitigation strategy to reduce S. Heidelberg virulence.
Keywords: Acetate kinase; Phosphotransacetylase; Secretion system apparatus; Type III secretion system